Penggunaan Instagram Oleh Remaja di Sekitar Wilayah Jalan Cenderawasih Kota Makassar - Emanuel Omedetho Jermias; Abdul Rahman; Muhammad Nur Awal (Jurnal Penelitian Multidisiplin Ilmu, 2022)
This article generally elaborates on the use of Instagram by teenagers in the Cenderawasih Street area, Makassar City. The type of research is descriptive qualitative research, namely research that describes certain situations based on data obtained in detail through observation, interviews with informants who provide information about the role of Instagram among teenagers. The results of this study indicate that: 1). Instagram has a role in adolescent lifestyles for self-existence and guidelines in dress procedures. 2). Instagram then became a trend among teenagers because Instagram can be used as a communication medium, besides that Instagram also acts as a source to get information as well as a place to fill spare time in this case get entertainment. 3). Instagram can have an impact on the social and economic conditions for teenagers